Medium temperature sintered BaTiO3-based ceramics for X8R capacitors - Xinyue Zhang; Junlei Qi; Yiqian Liu; Jinghan Cai; Yuan-hua Lin (Journal of Materiomics)
The development of X8R BaTiO3-based dielectric materials is of great significance for the high-temperature application of MLCCs. Herein, a series of BaTiO3-based dielectric ceramics were prepared by the conventional solid-state method, and the effects of Bi4Ti3O12 and Mn3O4 on the properties of BaTiO3-based dielectric ceramics were studied. The SEM images show that the addition of Bi4Ti3O12 with a low melting point can densify the ceramics at a lower sintering temperature (1,150 °C). TEM images and EDS results indicate that the samples have a “core-shell” structure, which can be optimized by Bi4Ti3O12, resulting in phase transition dispersion and thus improving the temperature stability of the material. The addition of Mn can reduce the dielectric loss of ceramics at high temperatures. As a result, the optimal composition exhibits a high permittivity of 2,090, a low dielectric loss of 1.1%, and high temperature stability satisfying the X8R specification.